INFLUENCE OF MOTHER ROOT SIZE AND PLANT SPACING ON CARROT SEED PRODUCTION - Anjum, Muhammad Akbar; Amjad, Muhammad (Journal of Research (Science), 2002)
Mother root size used had no significant effect on sprouting of stecklings, subsequent growth and seed yields. Plant spacing had significant influence on number of branches per plant from the base and seed yields per plant and per hectare. Maximum number of branches was produced in case of wider spacings (i.e. 45 and 30 cm). Highest seed yield per plant was recorded in widest spacing (i.e. 45 cm). However, seed yield per hectare was highest in closest plant spacing (15 cm). While, sprouting percentage of stecklings, plant height at flowering stage and average seed weight per umbel had no significant response to these plant spacings. As far as the interaction between these factors is concerned, stecklings either from very large sized roots or from large sized roots and planted in widest spacing resulted in the highest seed yield per plant. However, the highest seed yield per hectare was obtained from the combinations; very large sized roots x the closest spacing and large sized roots x the closest spacing due to more number of plants per hectare.